The impact of selenium yeast and vitamin E in blood profile and egg production of laying hens at the end of egg production period - Ismoyowati, I.; Rosidi, R.; Hidayat, N.; Yakubu, M. A. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
This study investigated the effects of selenium yeast and vitamin E supplementation on hematological parameters, egg production, and quality in laying hens aged beyond 94 weeks. The experiment adhered to ethical regulations and employed a Completely Randomized Design Dietary treatments included a basal diet (T0), or a basal diet supplemented with 0.450 mg selenium yeast and 100 mg vitamin E (T1), 0.675 mg selenium yeast and 100 mg vitamin E (T2), 0.450 mg selenium yeast and 200 mg vitamin E (T3), 0.675 mg selenium yeast and 200 mg vitamin E per kg diet (T4). There were 125 hens divided in five treatments and five replicates that contained five hens per replicate. Hematological parameters, egg production, and egg quality were determined. The T4 treatment reduced red blood cell counts (P<0.05), potentially impacting erythropoiesis. The T3 treatment increased lymphocyte content and decreased heterophil/lymphocyte ratio (P<0.05), which concurs with an increase in egg weight, egg mass, and Haugh Unit, and decreased feed conversion ratio (P<0.05). Thus, this study demonstrated that incorporating these supplements with the specified dosage (0.450 mg selenium yeast and 200 mg vitamin E per kg diet) in aged laying hens can enhance productivity and egg quality at the end of the production cycle.